The treatment of a loose submerged subgrade using dynamic compaction - Hamidi, Babak; Nikraz, Hamid; Varaksin, S. (Chinese Society of Pavement Engineering, 2011)
It is not unforeseeable to have pavements that have lost functionality and drivability due to excessive total, differential or creep settlements; liquefaction; or local shear failures of the subgrade layer. If the subgrade material does not have the necessary strength, it may be mandatory to carry out a ground treatment program to improve the ground conditions and to allow the safe construction of the subsequent layers. The causeway of Abu Dhabi to Reem Island has been constructed by reclaiming the approach road on the two sides of the bridge from the sea. The 8-m thick reclamation was performed by dumping sand into the sea. Geotechnical tests indicated that the reclaimed material did not meet the design requirements for constructing the bridge's approach roads and the foundations of the mechanically stabilized earth (MSE) walls. Dynamic Compaction was carried out to improve the ground conditions of the reclamation. Upon completion of soil improvement, pressuremeter tests were performed to verify the results. The test results demonstrated that the design and acceptance criteria were achieved.